Synthesis of bimetallic core-shell nanoparticles for photocatalysis - Tee, Hui Min (Nanyang Technological University, 2022)
The ongoing energy and environmental issues have always been the major roadblocks to progressing towards environmental sustainability, the fundamental of long-term growth. Photocatalysis can be regarded as a potential solution to the existing issues, with the catalysts playing a crucial role in the photocatalytic HER reaction. Unfortunately, the problems of photocatalysts includes the widespread application of Pt-based catalysts is hampered by its scarcity and high cost, as well as the practicality of bimetallic core-shell nanoparticles as catalysts, and difficulty in producing evenly distributed, monodispersed core-shell nanoparticles as catalysts. As a result, several efforts have been undertaken to design a higher efficiency photocatalyst. Although it is simple to study the photocatalytic process, however, novel bimetallic core-shell catalysts are seldom discovered. Herein, this study aims to advance beyond previous studies by developing a one-pot thermal decomposition method to synthesise a small size distribution and proximity close to monodispersed Ag@Ni bimetallic core-shell NPs with catalytic and magnetic functions through the monitored growth of the Ni-shells and Ag-cores. In addition, this report will investigate the controlled approach of particle size of Ag@Ni bimetallic core-shell NPs as well as how their optical, magnetic, and catalytic performance can be affected by the shell-thickness of the NPs. For comparison, size-controlled noble Ag NPs as well as magnetic transition Ni NPs will also be synthesised using similar procedure. Furthermore, through simple reflux treatment of the as-prepared monometallic and bimetallic NPs with GCN nanosheets in solvent, the photocatalytic ability will be examined. Results obtained from the photocatalytic HER revealed that the synthesised Ag@Ni bimetallic core-shell NPs improved photocatalytic performances and can be employed as an outstanding catalyst to produce high purity hydrogen to meet the growing needs for renewable energies.